Current Knowledge of Microglia in Traumatic Spinal Cord Injury - Xu, Lintao; Wang, Jingyu; Ding, Yueming; Wang, Linlin; Zhu, Yong-Jian (Frontiers in Neurology, 2022)
Microglia are the resident immune cells in the central nervous system (CNS). After traumatic spinal cord injury (SCI), microglia undergo activation, proliferation, and changes in gene and protein expression and morphology, with detrimental and beneficial effects. Activated microglia cause secondary neuronal injury via the production of proinflammatory cytokines, reactive oxygen species, and proteases. However, activated microglia also promote neuronal repair through the secretion of anti-inflammatory growth factors and cytokines. Proinflammatory cytokines increase endothelial permeability, promote A1 astrocyte activation and axonal demyelination, and reduce neural stem/progenitor cells (NSPCs), leading to the exacerbation of neuronal injury. In contrast, anti-inflammatory factors facilitate angiogenesis, reduce reactive astrocytes, and promote axonal remyelination and the propagation of NSPCs, contributing to tissue repair and locomotor recovery. Due to its limited regenerative capacity, the CNS requires beneficial microglia for continuous protection against injury. Understanding and regulating microglial activation status are beneficial to reducing detrimental effects and promoting repair behaviors and to obtain more information on efficient therapies for traumatic SCI. This review discusses microglial activation and the differences between microglia and similar immune cells, microglial interactions with other cells in the spinal cord, and the progress in the development of therapies targeting microglia in SCI.